Objective Assessment of Physical Activity and Associated Contexts During High School Sport Practices - Carlton, Troy; McKenzie, Thomas L.; Bocarro, Jason N.; Edwards, Michael; Casper, Jonathan; Suau, Luis; Kanters, Michael A. (Frontiers in Sports and Active Living, 2021)
Background: Organized sports provide children and adolescents with opportunities to achieve recommended amounts of moderate to vigorous physical activity (MVPA), and schools are a primary setting for sports programs. The main aims of this study were to examine participant physical activity (PA) levels during the most popular high school sports in the United States and to assess the influences of practice contextual factors on PA levels. Methods: Participant PA and its contexts were assessed during practices for the 10 most popular girls' and boys' high school sports in the United States. Data were obtained during 598 practice sessions in 12 schools in North Carolina using a validated direct observation instrument (System for Observing Fitness Instruction Time (SOFIT). A regression model was applied to understand the association between sport context and athletes' PA. Results: Overall, athletes were observed engaging in MVPA 60% of practice time. MVPA varied among sports and levels were highly influenced by practice contexts. Among girls' sports, cross country and soccer practices provided the highest proportion of MVPA and MVPA percent during boys' practice sessions was highest during cross country and track and field. Practice contexts were associated with MVPA accrual with time allocated for gameplay and fitness activities associated with the highest levels of PA. Conclusions: The results contribute to an understanding of which sports and how their practices are conducted facilitate increased PA. Findings indicate athletes accrue substantial amounts of PA during high school practices, but that it varies from sport to sport. As well, the context that characterizes sport practices is a significant determinant in how much PA occurs. Most sports that emphasized game simulation, fitness, and skill development drills had higher levels of MVPA. Given the length and frequency of practices and how the content is delivered, we can accurately predict how much PA athletes are likely to achieve during a given sport season. The findings from this study demonstrate that sport can make a useful, if not sufficient role in helping high school athletes reach recommended PA levels. PA engagement can be optimized by attending to the management of contexts surrounding the sports.